2016
DOI: 10.12948/issn14531305/20.4.2016.05
|View full text |Cite
|
Sign up to set email alerts
|

From Natural Language Text to Visual Models: A survey of Issues and Approaches

Abstract: Over the last 20 years, research groups focused on automating the process of extracting valuable information from Natural Language text in order to discover data and process models. In this context, several tools and approaches have been proposed. The overall objective of this survey is to examine existing literature works that transform textual specifications into visual models. This paper aims to give a comprehensive account of the existing tools meant to discover data and process models from natural languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The interest of an automatic technique for requirement analysis with natural language processing is shown in [2]. We used some equivalent methods and tools to transform textual specifications into visual models as detailed in [26] to design our approach. A Systematic Literature Review (SLR) on 13 studies highlights the systematic use of NPL techniques for feature identification on requirements described in natural language [5].…”
Section: Related Workmentioning
confidence: 99%
“…The interest of an automatic technique for requirement analysis with natural language processing is shown in [2]. We used some equivalent methods and tools to transform textual specifications into visual models as detailed in [26] to design our approach. A Systematic Literature Review (SLR) on 13 studies highlights the systematic use of NPL techniques for feature identification on requirements described in natural language [5].…”
Section: Related Workmentioning
confidence: 99%
“…The overview of existing solutions in the field of UML model creation from textual requirements and business process model creation from textual documents [27] showed that existing means allowed creating class diagrams, object diagrams, use case diagrams, and several of them provide composition of sequence, collaboration and activity diagrams. However, all the solutions have certain limitations, for example, some require user intervention, some cannot perform analysis of irrelevant classes, some require structuring a text in a certain form before processing, and some cannot correctly determine several structural relationships between classes.…”
Section: Related Workmentioning
confidence: 99%
“…However, all the solutions have certain limitations, for example, some require user intervention, some cannot perform analysis of irrelevant classes, some require structuring a text in a certain form before processing, and some cannot correctly determine several structural relationships between classes. The only approach mentioned by the authors [27] that allows deriving a complete business process model is presented by Friedrich, Mendling and Puhlmann [28].…”
Section: Related Workmentioning
confidence: 99%